KINETIC TRANSFORMATION OF SPINEL TYPE LiMnLiMn2O4 INTO TUNNEL TYPE MnO2 - Daud K Walanda (Universitas Gadjah Mada, 2007)
Lithiated phase LiMn2O4 is a potential cathode material for high-energy batteries because it can be used in conjunction with suitable carbon anode materials to produce so-called lithium ion cells. The kinetic transformation of LiMn2O4 into manganese dioxide (MnO2) in sulphuric acid has been studied. It is assumed that the conversion of LiMn2O4 into R-MnO2 is a first order autocatalytic reaction. The transformation actually proceeds through the spinel l-MnO2 as an intermediate species which is then converted into gamma phase of manganese dioxide. In this reaction LiMn2O4 whose structure spinel type, which is packing between tetrahedral coordination and octahedral coordination, is converted to form octahedral tunnel structure of manganese dioxide, which is probably regarded as a reconstructive octahedral-coordination transformation. Therefore, it is a desire to investigate the transformation of manganese oxides in solid state chemistry by analysing XRD powder patterns. Due to the reactions involving solids, concentrations of reactant and product are approached with the expression of peak areas.